IP-Enabled C/C++ Based High Level Synthesis: A Step towards Better Designer Productivity and Design Performance. (8th January 2014) - Sinha, Sharad; Srikanthan, Thambipillai
Abstract : Intellectual property (IP) core based design is an emerging design methodology to deal with increasing chip design complexity. C/C++ based high level synthesis (HLS) is also gaining traction as a design methodology to deal with increasing design complexity. In the work presented here, we present a design methodology that combines these two individual methodologies and is therefore more powerful. We discuss our proposed methodology in the context of supporting efficient hardware synthesis of a class of mathematical functions without altering original C/C++ source code. Additionally, we also discuss and propose methods to integrate legacy IP cores in existing HLS flows. Relying on concepts from the domains of program recognition and optimized low level implementations of such arithmetic functions, the described design methodology is a step towards intelligent synthesis where application characteristics are matched with specific architectural resources and relevant IP cores in a transparent manner for improved area-delay results. The combined methodology is more aware of the target hardware architecture than the conventional HLS flow. Implementation results of certain compute kernels from a commercial tool Vivado-HLS as well as proposed flow are also compared to show that proposed flow gives better results.